2023
DOI: 10.3390/agriculture13020278
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Algorithm Optimization of Liquid Manure Spreading Control

Abstract: The growth of field crops needs appropriate soil nutrients. As a basic fertilizer, liquid manure provides biological nutrients for crop growth and increases the content of organic matter in crops. However, improper spraying not only reduces soil fertility but also destroys soil structure. Therefore, the precise control of the amount of liquid manure is of great significance for agricultural production and weight loss. In this study, we first built the model of spraying control, then optimized the BP neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Pengju Wang et al [5] addressed the issue of low precision in the fertilization control device for tractor-trailer applications and proposed a genetic algorithm-optimized Back Propagation Neural Network (BP) PID control algorithm. Test results show an average relative error of 1.07% in liquid manure flow and an actual response time of 2.85 s. However, in practical operation, the system requires a longer time to compute optimal parameters, thus affecting the real-time performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Pengju Wang et al [5] addressed the issue of low precision in the fertilization control device for tractor-trailer applications and proposed a genetic algorithm-optimized Back Propagation Neural Network (BP) PID control algorithm. Test results show an average relative error of 1.07% in liquid manure flow and an actual response time of 2.85 s. However, in practical operation, the system requires a longer time to compute optimal parameters, thus affecting the real-time performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Pengjun Wang et al [6] proposed a Back-Propagation (BP) Neural Network PID (Proportional-Integral-Derivative) control algorithm based on Genetic Algorithm (GA) optimization. Their simulation results indicated that this control algorithm exhibited excellent stability, a short response time, and minimal overshoot, achieving precise fertilization effects.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers described precise identification and positioning systems ("eyes"); these studies applied the improved YOLO algorithm to the recognition of tea and apples [18,19]. Two papers described sensitive decision-making and control systems ("brain") [20,21]; these studies use intelligent control algorithms, such as BP neural network algorithms, to control actuating components or for fault diagnosis. These papers address harvesting components, traveling mechanisms, sensing systems and decision-making algorithms for a wide range of crop harvesters, including grains, vegetables and fruits.…”
mentioning
confidence: 99%